CONDITIONAL SIMULATION OF NONGAUSSIAN RANDOM FUNCTIONS - Emery X. (My University, 2002)
This paper presents a conditional simulation procedure that overcomes the limits of gaussian models and enables one to simulate regionalized variables with highly asymmetrical histograms or with partial or total connectivity of extreme values. The philosophy of the method is similar to that of sequential indicator technique, but it is more accurate because it is based on a complete bivariate model by means of an isofactorial law. The resulting simulations, which can be continuous or categorical, not only honor measured values at data points, but also reproduce the mono and bivariate laws of the random function associated to the regionalized variable, that is, every one or two-point statistic: histogram, variogram, indicator variograms. The "sequential isofactorial" method can also be adapted to conditional simulation of block values, without resorting to point-support simulations.
Keywords: SEQUENTIAL INDICATOR SIMULATION; ISOFACTORIAL MODELS; DISJUNCTIVE KRIGING; BIVARIATE DISTRIBUTION